REGADENOSON MYOCARDIAL PERFUSION SCINTIGRAPHY: A SINGLE CENTRE EXPERIENCE - Adil, Muhammad; Zaigham Salim Dar; Shahbaz Afsar Khan; Fida Hussain; Asad Malik; Husnain Saleem (Journal of Ayub Medical College Abbottabad, 2024)
Background: Regadenoson is highly selective A2A adenosine receptors agonist used for stress myocardial perfusion scintigraphy. This study presents our initial experience utilizing Regadenoson as a myocardial perfusion stress agent, aimed to assess the safety of Regadenoson for stress myocardial perfusion scintigraphy. Methods: Following Institutional Ethical Review Borad approval, adult patients presenting for myocardial stress perfusion scintigraphy were included using non-probability consecutive sampling. Exclusions included second or third-degree AV block, unstable angina, recent myocardial infarction, severe hypotension, or significant heart failure. Demographic data, co-morbidities, vitals, and adverse events were recorded. Results: Sixty-three patients were included, predominantly male (63.5%), with a mean age of 56.81±12.95 years. Hyperlipidaemia was the most common co-morbidity (47.6%). Systolic and diastolic blood pressure decreased acutely but normalised by 60 minutes. No serious adverse effects occurred, though transient ST segment depression was noted in 8.3% of patients. The most common adverse effects were dyspnoea (23.8%) and headache (21.4%). Conclusion: Regadenoson is associated with transient haemodynamic changes and non-serious transient adverse effects.